2018
DOI: 10.1016/j.ebiom.2018.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of the safety and pharmacodynamics of inhaled interleukin-13 monoclonal antibody fragment VR942

Abstract: Background Interleukin-13 (IL-13) is a key mediator of T-helper-cell-type-2 (Th-2)-driven asthma, the inhibition of which may improve treatment outcomes. We examined the safety, pharmacokinetics, pharmacodynamics, and immunogenicity of VR942, a dry-powder formulation containing CDP7766, a high-affinity anti-human-IL-13 antigen-binding antibody fragment being developed for the treatment of asthma. Methods We conducted a phase 1, randomized, double-blind, placebo-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…stages of clinical evaluations, most with attractive safety profile. Several mAbs have also been clinically evaluated as inhaled aerosols with demonstrated preliminary safety and tolerability(6, 16,37,38), suggesting the practicality of formulating 1212C2 for selfadministered inhalation. Over 90% of all symptomatic COVID-19 patients are not hospitalized, but they all still need treatment to minimize the potential for transmission and limit complications from viral infection.…”
mentioning
confidence: 99%
“…stages of clinical evaluations, most with attractive safety profile. Several mAbs have also been clinically evaluated as inhaled aerosols with demonstrated preliminary safety and tolerability(6, 16,37,38), suggesting the practicality of formulating 1212C2 for selfadministered inhalation. Over 90% of all symptomatic COVID-19 patients are not hospitalized, but they all still need treatment to minimize the potential for transmission and limit complications from viral infection.…”
mentioning
confidence: 99%
“…For example, there are three anti-TNF agents -a nanobody, a decoy receptor and a mAb -with an oral administration route for treatment of Crohn's disease and ulcerative colitis in clinical trials, of which the nanobody V565 is the most advanced, having reached phase II trials 117 . An inhaled formulation of a high-affinity antibody fragment, abrezekimab, that targets IL-13 was well tolerated in a phase I safety trial, and is proposed to provide a more rapid onset of action at lower doses than subcutaneous systemic administration for the treatment of asthma 118 .…”
Section: Platform Choices May Influence Therapeutic Effects In Differmentioning
confidence: 99%
“…Since the promising Phase II results for lebrikizumab [ 5 ] and tralokinumab [ 4 ] were not confirmed in Phase III trials, a better understanding of the responder population for anti-IL-13 blockade is necessary. In this issue, the study of Burgess et al [ 6 ] provide data of the administration of a humanized, high-affinity, neutralizing, anti-human-IL-13 antibody fragment, administered through the inhaled route, giving an alternative to the systemic administration of monoclonal antibodies for the therapy of asthma and mimicking the usual practice of drug delivery in asthmatic patients. This study has a proof-of-concept element, as the observed FeNO suppression shows an anti-inflammatory effect of this agent, while the numerical increase of FEV 1 (with a mean difference of 150–200 mL versus placebo) shows an important treatment efficacy, both these improvements need to be confirmed in later phase trials.…”
mentioning
confidence: 99%
“…The difference in efficacy of this inhaled anti IL-13 antibody compared to injectable anti-IL-13 medicines is something that needs to be considered, as this potential option moves along its development pathway. The fact that in the study of Burgess et al [ 6 ] there is a lack of a dose-response relationship for both FeNO and FEV 1 is a potential issue that needs to be considered in future trials of this agent.…”
mentioning
confidence: 99%
See 1 more Smart Citation